Histopathological Comparison between Punch and Full Thickness Rectal Biopsy in Diagnosis of Hirschsprung’s Disease (KYAMC Journal, 2022)
Background: The diagnosis of Hirschsprung’s disease (HD) is dependent on the histological study of rectal ganglion cells. Open rectal biopsy is the mainstay that requires general anesthesia (GA) and carries risk of many complications. Rectal punch biopsy has gained wide acceptance and has become the choice as it is simple, safe, having no need of anesthesia, done bedside with a simple biopsy forcep with high degree of accuracy and virtual absence of any complications.Objective: To find out the efficacy of rectal punch biopsy in the diagnosis of Hirschsprung’s disease.Materials and Methods: A cross sectional descriptive observational study was carried out with the histological findings of 60 rectal punch biopsies with corresponding 60 full thickness rectal biopsies from 60 suspected HD patients from March 2018 to February 2020. Sections made from the paraffin blocks were stained with H&E and were examined for the presence or absence of ganglion cells and hypertrophic nerve fibers in the submucosa. Then the relations were studied. These findings were compared with full thickness rectal biopsy.Result: There were 40(66.7%) cases of male and 20(33.3%) cases of female including 26 (43.3%) cases of infants. Out of 60 cases, 10 cases (seven inadequate and three suspicious) of punch biopsy were not compared with full thickness rectal biopsy. Out of 50 cases, 38(63.3%) cases were HD in punch biopsy; among these 36(92.3%) cases were HD and 2(18.2%) cases were Non-HD in full thickness rectal tissue biopsy. The accuracy of punch biopsy was measured by sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and efficiency of the test which were 92.3%, 81.8%, 94.7%, 75.0% and 90.0% respectively.Conclusion: The rectal punch biopsy is simple, safe, no need of anesthesia and can be done with a simple biopsy forcep with high degree of accuracy.KYAMC Journal Vol. 13, No. 01, April 2022: 37-40